Impact of infant 13-valent pneumococcal conjugate vaccine on serotypes in adult pneumonia - Rodrigo, Chamira; Bewick, Thomas; Sheppard, Carmen; Greenwood, Sonia; Mckeever, Tricia M; Trotter, Caroline L; Slack, Mary; George, Robert; Lim, Wei Shen (The European respiratory journal, 2015)
Infant 13-valent pneumococcal conjugate vaccination (PCV13) was introduced to the UK in 2010. Its impact on serotypes implicated in adult non-bacteraemic pneumococcal pneumonia is not known. Beginning in 2008, a 5-year prospective cohort study of adults admitted to hospital with community-acquired pneumonia (CAP) was conducted. Pneumococcal serotype was established using a validated multiplex immunoassay (Bio-Plex; Bio-Rad, Hercules, CA, USA). The overall incidence for hospitalised CAP and pneumococcal CAP was 79.9 (95% CI 76.6-83.3) and 23.4 (95% CI 21.6-25.3) per 100,000 population, respectively. A decline in CAP (incidence rate ratio (IRR) per year 0.96, 95% CI 0.94-0.99; p=0.016) and pneumococcal CAP (IRR per year 0.84, 95% CI 0.80-0.89; p<0.001) was observed over the 5-year period of the study. Between the pre- and post-PCV13 periods of the study, the incidence of CAP due to serotypes included in the PCV7 declined by 88% (IRR 0.12, 95% CI 0.08-0.20; p<0.001), and CAP due to the additional 6 serotypes in PCV13 declined by 30% (IRR 0.70, 95% CI 0.51-0.96; p=0.024). Incidence of adult pneumococcal pneumonia declined over the last 5 years, with serotypes included in PCV13 declining post-PCV13 introduction, indicating early herd protection effects from PCV13 infant vaccination on adult non-bacteraemic disease. These effects may accrue over the coming years with implications for national pneumococcal vaccination policies in adults.